2020
DOI: 10.1016/j.celrep.2020.107761
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin-D-Binding Protein Contributes to the Maintenance of α Cell Function and Glucagon Secretion

Abstract: Highlights d Vitamin-D-binding protein (DBP) is highly expressed in pancreatic a cells d Glucagon secretion and insulin tolerance are altered in mice lacking DBP d DBP-null a cells possess an abnormal actin cytoskeleton and are dysfunctional d DBP levels are decreased in a cells of donors with late-onset type 1 diabetes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 63 publications
0
28
0
Order By: Relevance
“…Whether these results are associated with the beta cell de-differentiation seen in T2DM is not known, but it will be interesting to confirm findings in human samples. DBP is also expressed in delta cells, confirmed using both RNA-seq (Adriaenssens et al, 2016) and immunohistochemistry (Viloria et al, 2020), although its downstream functions are unknown. Cell-specific manipulation of DBP in the islet compartment will therefore be integral to any approaches targeting DBP as a diabetes treatment, perhaps using molecular addresses specific to alpha cells.…”
Section: Other Islet Targets For Dbpmentioning
confidence: 87%
See 2 more Smart Citations
“…Whether these results are associated with the beta cell de-differentiation seen in T2DM is not known, but it will be interesting to confirm findings in human samples. DBP is also expressed in delta cells, confirmed using both RNA-seq (Adriaenssens et al, 2016) and immunohistochemistry (Viloria et al, 2020), although its downstream functions are unknown. Cell-specific manipulation of DBP in the islet compartment will therefore be integral to any approaches targeting DBP as a diabetes treatment, perhaps using molecular addresses specific to alpha cells.…”
Section: Other Islet Targets For Dbpmentioning
confidence: 87%
“…Despite the known (potent) biological functions of DBP, an effect on alpha cell physiology has only recently been examined. Using DBP-null mice, we were able to show that loss of DBP results in major alpha cell impairments (Viloria et al, 2020) (Figure 3). Mice deleted for DBP displayed reductions in insulin-and low glucose-stimulated glucagon release.…”
Section: Dbp As An Alpha Cell Regulatormentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, transgenic mice overexpressing VDR in beta cells are protected against streptozotocin-induced diabetes and exhibit preserved beta-cell mass, along with reduced islet inflammation [142]. Interestingly, a recent study [143] showed that DBP is highly expressed in murine and human alpha cells, and loss of DBP gives rise to alterations in alpha-cell number and size, electrical activity and glucagon secretion in vitro and in vivo. Additionally, authors found reduced expression levels of DBP in islets of donors with late-onset or long-standing T1D [143].…”
Section: Role Of Vitamin D In Autoimmune Diabetes: T1d and Ladamentioning
confidence: 99%
“…), a-and islet-cell lineage transcription factors (MAFB, FEV, NKX2.2, NEUROD1), G-protein coupled receptors known to impact a-cell function (GIPR, SSTR1, FFAR1, GPR119), and secreted factors implicated in islet function or development (LOXL4, WNT4, UCN3, IL16). Significant negative correlates were less abundant but included the vitamin D binding protein (GC) which is known to regulate a-cell Na + currents (Viloria et al, 2020). GSEA for KEGG Although a-cell lineage markers correlate with Na + current activity, the high degree of overlap in the Na + current properties between human a-and b-cells make it impossible to use Na + currents alone to interrogate shifts in human a-cell phenotypes.…”
Section: Electrophysiological Fingerprint Modelling Links Human A-cell Behavior and Cell Phenotypementioning
confidence: 99%